Social impact analysis and mitigation measures of the ecological solid waste management system of Los Baños, Laguna - Tapay, Nenita E. (Animo Repository, 2008)
This study presents a social impact analysis of the ecological solid waste management system (ESWMS) of Los Baños, Laguna, as well as the mitigation measures necessary to reduce the level of its negative impacts on the social environment. The social impact analysis utilizes the matrix format prescribed by the European Commission (2005). Rows of the matrix reveal the main policy options and the concurrent actions. The columns of the matrix show the main types or categories of impacts organized according to a time horizon. Each cell presents the likelihood of an impact whether it is certain, probable, or unlikely. It is also indicated in each cell whether the impact is expected to be positive or negative and its magnitude, or uncertain. Affected population and the time scale over which the impacts are expected to occur are also indicated in another cell. The study found that negative impacts centered on the settlers in the former Los Baños "smoking dumpsite" turned eco-waste processing center. Used at anchoring their survival on the dumpsite, these settlers were relocated to the town proper. They earned income at present from new sources: the garbage pick-up stations from different barangays (villages) in the municipality and garbage from the households. Key informant interviews have revealed that these settlers often become suspects of petty crimes like theft in the municipality. Mitigation measures highlighted in the study are their inclusion to the Los Baños Solid Waste Organization-- the people's organization of waste pickers officially recognized and trained by the local government unit of Los Baños and skills enhancement training on various livelihood programs. These were geared towards waste reuse, reduction and recycling of plastics into furniture mono blocks and production of alternative packaging materials from waste.